Leadership Style, Community Participation, and Development Success: The Mediating Role of Village Apparatus Capacity - Sopiansyah Sopiansyah; Titin Ruliana; Andi Indrawati (Goodwood Publishing, 2026)
Purpose: This study examines the influence of leadership style and community participation on the success of development projects in Kombeng District, East Kutai Regency, with the mediating role of village apparatus capacity. Research Methodology: A quantitative, cross-sectional design was employed, gathering data from 150 purposively selected respondents, including community members and village officials. A structured questionnaire was used to measure leadership style, community participation, village apparatus capacity, and development success. Reliability and validity were confirmed through expert review and pilot testing. Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized to analyze relationships and mediation effects. Results: The findings indicate that community participation directly enhances development success, while leadership style does not have a direct effect. However, both leadership style and community participation exert significant indirect effects on development success through village apparatus capacity. Conclusions: The study concludes that fostering active community engagement and strengthening the capacity of village apparatus are crucial for sustainable development. It recommends initiatives to enhance participatory mechanisms and leadership development to improve village apparatus competencies. Limitations: The study is limited by its focus on Kombeng District and the cross-sectional design, which may limit generalizability and causal inferences. Contributions: This research highlights the mediating role of village apparatus capacity and offers practical insights for enhancing participatory governance and leadership effectiveness in local development initiatives.